Intellectual Disability among Dutch Homeless People: Prevalence and Related Psychosocial Problems - Van Straaten, Barbara (Public Library of Science, 2014)
BACKGROUND: There is a higher prevalence of intellectual disability (ID) among homeless people than in the general population. However, little is known about the additional psychosocial problems faced by homeless people with ID. We describe the prevalence of ID in a cohort of homeless people in the Netherlands, and report relationships between ID and psychosocial problems in terms of psychological distress, substance (mis)use and dependence, as well as demographic characteristics in this cohort. METHODS: This cross-sectional study is part of a cohort study among homeless people in the four major cities of the Netherlands. Data were derived from 387 homeless people who were interviewed and screened for ID six months after the baseline measurement. Multivariate logistic regression analyses and χ(2) tests were performed to analyze relationships between ID, psychosocial problems and demographic characteristics. FINDINGS: Of all cohort members, 29.5% had a suspected ID. Participants with a suspected ID had a higher mean age, were more likely to be male and to fall in the lowest category of education than participants without a suspected ID. Having a suspected ID was related to general psychological distress (OR  = 1.56, p<0.05), somatization (OR  = 1.84, p<0.01), depression (OR  = 1.58, p<0.05) and substance dependence (OR  = 1.88, p<0.05). No relationships were found between a suspected ID and anxiety, regular substance use, substance misuse and primary substance of use. CONCLUSION: The prevalence of ID among Dutch homeless people is higher than in the general population, and is related to more psychosocial problems than among homeless people without ID. Homeless people with a suspected ID appear to be a vulnerable subgroup within the homeless population. This endorses the importance of the extra attention required for this subgroup.